Profil Berat Molekul Enzim Bromelain dari Bonggol Nanas (Ananas Comosus) dengan Metode Elektroforesis SDS-PAGE - Nita Magfirah Ilyas (Indonesian Journal of Science and Public Health, 2024)
Bromelain is found in all pineapple plant tissues. About half of the protein in pineapple contains the protease bromelain. Bromelain has been used in the food and health industry for various purposes, such as accelerating wound healing, helping digestion, increasing drug absorption, increasing immunity. The aim of this research was to determine the molecular weight profile of the bromelain enzyme from pineapple core (Ananas comosus) using the SDS-PAGE (Sodium Dodecyl Sulphate Poly Acrylamide Gel Electrophoresis) electrophoresis method. The bromelain purification process begins with multistage precipitation using ammonium sulfate, followed by a dialysis process. The purification process was continued with ion exchange column chromatography method by using DEAE-Sepharose. Furthermore, the molecular weight of enzyme solution were determined using SDS-PAGE method. Further purification using Diethylaminoethyl-Sepharose (DEAE-Sepharose) ion exchange column chromatography showed an increase in specific activity and purity level to 500 U/mg with a purity level of 4.901 times the crude enzyme extract. The molecular weight of the enzyme fraction purified with DEAE-Sepharose has a molecular weight range of 21.5-31 kDa. The synthesized enzyme fraction has a molecular weight range that is relatively the same as standard bromelain, ranging from 28-30 kDa.